Yun-tai Chen receives 2010 international award - Das, S; Chen, Y (2011)
Yun-tai Chen received the International Award at the 2010 AGU Fall Meeting Honors Ceremony, held on 15 December 2010 in San Francisco, Calif. The award honors an individual scientist or a small team for making an outstanding contribution to furthering the Earth and space sciences and using science for the benefit of society in less favored nations.